Computer networking bible : 3 in 1. The complete crash course to effectively design, implement and manage networks. Including sections on security, performance and scalability - Worely, Rick C. (Rick C. Worley, 2024)
"Specially written for the non-tech-savvy user, this concise and comprehensive handbook reveals how you can design, implement, and manage any computer network. Inside, you’ll discover the essential hardware that forms the backbone of a computer network, the must-know protocols that keep everything running smoothly, and how you can effectively secure your network to protect it from malicious users. Divided into 3 unique books that aim to give you a complete overview of the fundamentals behind networking, the Computer Networking Bible shares easy-to-digest advice and straightforward explanations, so that you can build your confidence and learn at your own pace as you deepen your knowledge of the essential technologies you use every day."--Back cover.